Study of cohesive sediment using ultrasound - Othman A. Karim,; Martin Crapper,; Ali, K. H. M. (Universiti Kebangsaan Malaysia, 1997)
The study of cohesive sediment in the laboratory gives rise to a number of instrumentation problems, especially in the location of mud bed, fluid mud and hindered settling layers and in the measurement of flow velocities. This paper describes the application of medical diagnostic ultrasound technique in the cohesive sediment study conducted at the University of Liverpool, United Kingdom. This paper illustrates that the use of ultrasound technique creates a reasonably flexible environment for the study of fluid mud phenomenon in which bed formation and flow velocities can be measured easily, accurately and non-intrusively. This in turn will assist in development of computer models to predict the environmental impact, siltation rates and dredging requirements in both new and existing ports and harbour developments.